Error Analysis Made by EFL Learners in Writing Pronoun (Academic Year 2015) at English Department at FKIP UHN Pematangsiantar - Reina Adelina Sipahutar; Eden Pasaribu (Universitas Bunda Mulia, 2018)
This research is about Error Analysis Made By EfL Learners In Writing Pronoun (Academic Year 2015) At English Department At Fkip Uhn Pematangsiantar. Error are any deviation from the standard grammar of the target language, while the personal pronoun is reffering to a person or thing. This research focused on the problem about (1) What types of errors produced by English learners in using Pronoun on the fourth semester in FKIP UHN Pematangsiantar? (2) What are the percentage of errors produced by English learners in using pronoun on the fourth semester in FKIP UHN Pematangsiantar? (3) What are the causes of errors produced by English learners in using Pronoun on the fourth semester in FKIP UHN Pematangsiantar? To answer the question of the problem, the writer follows some theories House and Harman (1931), Curme (1947), Meade et al. (1964), Harris (1969), Frank (1972), Corder (1973), Brown (1980), Abbot (1981), Brown (2000), Pyle and Munoz (2002), Arikunto (2006) to analyzed the data. The learners are sitting in the class of Language Metafunction in 2017 (Academic Year 2015). The writers will choose 20 students from each of the three classes (Group A, B, and C). The total numbers of the subject is 60 EFL learners.The data Shows that. The writer finds out that the Error of Addition (29 errors or 6,15%), Error of Omission (175 or 371%), Error of Substitution (225 error or 47,77%) and Error of Ordering (42 error or 8,91%). The dominant type of error was substitution errors (225 error or 47,77%). The mean is 16,54 and standard deviation is 7,17. The test is valid where the validity is 0.55.The test is also reliable where the reliability is 0.88. The average of the right score is 17 items out of 30 items and the percentage is 55,14 %. The average of the wrong score (error score) is 13 items out of 30 items and the percentage is 44,85 %. Finally the writer suggests to the English teachers to have a good teaching strategy to explain the use of personal pronoun. Keywords: error, personal pronoun, teaching